Multimodal Teaching in EFL Context: A Literature Review - Ni Komang Arie Suwastini; Putu Dita Marantika; Ni Luh Putu Sri Adnyani; Made Astawa Kusuma Mandala; Ni Nyoman Artini (Edu-Ling: Journal of English Education and Linguistics, 2021)
In the 21st century, the development of technology has made a lot of influence on the educational process. Technology brings many new approaches to the classroom such as multimodal teaching. The current study intended to review the implementation and effectiveness of multimodal teaching in the context of English language teaching. The review followed Aveyard's (2010) design, with the criteria of selecting the articles used as sources of data are research articles from journals. The result of the review found that the characteristics, benefits, and procedures of multimodal teaching vary greatly according to the needs and abilities of teachers to design the teaching and learning activities. The review also found that multimodal teaching affected students' motivation, productive skills, reading skills, and learning autonomy. This study suggests the implementation of multimodal teaching in ELT classrooms.